Investigation of magnetically controlled electric arc - Biloborodchenko, Volodymyr; Dzyubyk, Andrii; Zabranskyi, Andrii (Lviv Politechnic Publishing House, 2017)
In this work, the results of pad welding with the circularly rotating arc existing in an inert gas between a circle cathode with the diameter suitable to dimensions and geometry of a welded surface, with the kinematic characteristics of the motion provided (with the rest equal conditions) by the external magnetic field, are considered. It is shown that the strict theory of an electric arc is insufficient for the description of real physical processes occurred in it under the action of external exciting magnetic fields, and so it does not allow conducting satisfactory technological calculations of the parameters of the pad welding process performed by the arc moved by the external magnetic field. The main problem consists in determining the effectiveness and the direction of superposition of electrodynamic and mechanical forces in it, which resist arc interaction with the magnetic field. Therefore, the aim of the work is to investigate the influence of the induction value В of the transvers magnetic field of a solenoid inductor on predicted kinematic characteristics of the arc. The investigations were conducted with the use of experimental equipment (test bench) consisting of a toroidal inductor with a winding. On the inductor, a nonfusible water-cooled ring copper electrode is mounted. Electrode dimensions agree with the diameter of pad surface. The shielding gas is provided through the system of radially located nozzles with discreet valvular operation, whose work priority is agreed with the arc motion velocity by a control unit. Since the values of abovementioned forces directly conditioned by the presence of a magnetic field in an interelectrode gap, the investigation of its intensity by the electrodynamic method with the help of the measuring instrument for magnetic induction ИМИ-1 was carried out. The analysis of the superimposed surface of the impact of the magnetizing current and the arc gap, which are used at pad welding by magnetically controlled arc, on the field induction shows that the range of their influence as technological mode parameters is quite narrow. Accordingly, for optimal choice of model nomographic solutions and the description of the correlation of parameters of the arc gap and magnetizing current, which provide the technologically suitable induction, an experiment was conducted according to the matrix of simplex-summarized С-С2 design. The investigations of a model extremum shows the acceptable induction value of 850∙10-5Т for the length of the electrode gap of 4 mm and inductor magnetizing current of 6 A. As a result, the proposed design of the test bench satisfies the geometrical parameters of renovated workpiece and enables using the effective repeated thermal pad cycle per unit of the surface by the rotating arc in the stable magnetic field. Settings of the magnetically operated arc, which provide the necessary value of field induction in the inter-electrode gap, can be determined either by nomograph solution, or by the strict statistic models. The influence of the length of the inter-electrode gap on the choice of the induction value is limited by technologically suitable pad current and corresponding length of an arc column. The main setting and controlling parameter of the magnetic field mode is the inductor magnetizing current. The force of resistance to arc motion at the stage of arc development and at the stage of arc steady motion is directly proportional to the value of the pad current. Calculated values of the velocity of arc motion at given values of the pad current are in the range relevant to its steady motion and provide the processes of anode melting without thermal damaging the ring cathode.
Keywords: pad welding; circularly rotating arc; inert gas; magnetic field; induction; interelectrode gap; pad current; anode melting; magnetizing current